Inadvertent Discovery of Gerstmann’s Syndrome During a Skull MRI and Its Anatomical Basis: A Case Report: Life Sciences- Anatomy - J Waghray, Nitya; P, Bheemesh; Rajasundaram, Dr. Archana; Johnson, Dr. W.M.S (International Journal of Life Science and Pharma Research, 2023)
A rare neurological disorder in which an individual is unable to perform tasks related to language, spatial recognition,mathematics, and cognition is known as Gerstmann’s syndrome(GS). Gerstmann hypothesised that the four symptoms thatmakeup Gerstmann’s syndrome are caused by a shared cognitive problem (Grundstörung). Gerstmann asserted that it is a bodyschema disorder that only affects the hand and fingers. Since then, the existence of a Grundstörung has been disputed. The studyproposed a shared psychoneurological element, but it should be connected to changes in mental pictures rather than the bodilyschema. The significant facts appear to be the common simultaneous impairment of writing, computation, and bodily awarenessafter left parietal lesion, beyond the diagnostic label of "pure" and "non-pure" Gerstamann’s syndrome instances. Some functionaldomains can be linked to patients’ symptoms despite being heterogeneous. A 65-year-old male was brought to the hospital witha history of injury to the head and complaints of confusion, speech difficulty, inability to perform simple calculations, severeheadache, and drowsiness. The patient was sent to the radiology department of Sree Balaji Medical College and Hospital,Chennai, for a Magnetic Resonance Imaging of Skull (MRI). The MRI study revealed chronic ischemic changes in periventricularand subcortical white matter in the parietal lobes. Certain ischemic changes were also observed in the frontal lobe, suggestingage-related changes and Gerstmann’s syndrome. By cutting off various portions of the inferior parietal cortex, a lesion affectingsubcortical and subangular bundles of fibers affects many circuits with distinct roles. Therefore, the deficits seen in the patientare best explained by this anatomical explanation.